2020
DOI: 10.1111/aej.12417
|View full text |Cite
|
Sign up to set email alerts
|

Are the evaluation criteria used in preclinical endodontic training courses relevant? A preliminary study

Abstract: This study aimed to evaluate the relevance of a conventional evaluation protocol (CEP) for preclinical endodontic training. Seven dental students performed root canal treatments on an extracted human molar which was then evaluated by CEP (clinical and radiographic observations, including preparing the access cavities, preparing and filling the root canal, and detecting iatrogenic errors). A reference evaluation protocol (REP) based on micro‐computed tomographic images analysis was used as a control. The evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In our study, all the steps of the endodontic treatment were evaluated, in accordance with Vantorre et al [25]. Root canal treatments are step-by-step interdependent, so it is reasonable to evaluate each step individually rather than to just evaluate the nal result.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all the steps of the endodontic treatment were evaluated, in accordance with Vantorre et al [25]. Root canal treatments are step-by-step interdependent, so it is reasonable to evaluate each step individually rather than to just evaluate the nal result.…”
Section: Discussionmentioning
confidence: 99%
“…Studies considering taper had reported lower frequencies of adequate root canal treatment [9,10,30]. Taper is a subjective matter that cannot be adequately re ected in a two-dimensional radiograph, moreover, it may be in uenced by the canal's original anatomy giving the impression of a large taper irrespective of actual instrumentation [33]. Accordingly, it was excluded as an evaluation criterion in this study [25,32].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, all the steps of the endodontic treatment were evaluated, in accordance with Vantorre et al [ 25 ]. Root canal treatments are step-by-step interdependent, so it is reasonable to evaluate each step individually rather than to just evaluate the final result.…”
Section: Discussionmentioning
confidence: 99%